ANALISIS KOMPETENSI PEDAGOGIK MAHASISWA PENDIDIKAN EKONOMI YANG MELAKSANAKAN PPL-2 TAHUN 2017 - Br Siringo-ringo, Elisa; Ulfah, Maria; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to know the competence pedagogical on Economic Students who did the teaching practice in year 2017 in SMA of Pontianak. The research Methodology of this research is used Descriptive study which qualitative form. Thedata source ofthis research is the teachers and the economic BKK akuntansi studentsFKIP Tanjungpura University in did their teaching practice in year 2017 Pontianak.The research result showed that pedagogical competence on the students when they did teaching practice in understanding their studentsare in a broad manner and for the spesific is they were unconfidence of their ability, the students did the teaching learning process, such as they can manage their class well, they evaluated students result such as did the written or spoken test very well, analized students score to determine the completeness of their students, they were participatedÂ  to advance their students ability and also identified the students talent and interest by did the survey of students interest in study the Economic subject or not.Â Keywords: Pedagogical competence, teaching practice